"The Last Day of Don Juan’s Life" by Stanislav Zhevusky. Sources and inspirations - Szymańska, Aleksandra (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2013)
The aim of this article is to analyze possible literary influence on the drama The Last Day of Don Juan’s Life by the Polish writer S. Zhevusky. We took into consideration the biography of Zhevusky and the detailed analysis of his work and we proposed the thesis about the possible influences of French and Russian literature on the drama The Last Day of Don Juan’s life. As we could observed, the drama by Zhevusky showed some similarity (taking into account the language and the plot) to the following literary works: Don Juan by Moliere, Demon by M. Lermontov, The Stone Guest by A. Pushkin and Don Juan by A. Tolstoy.